Patient perceptions of visual, vestibular, and oculomotor deficits in people with Parkinson's disease. (2nd June 2020) - Berliner, Jean M; Kluger, Benzi M; Corcos, Daniel M; Pelak, Victoria S; Gisbert, Robyn; McRae, Cynthia; Atkinson, Christine C; Schenkman, Margaret
ABSTRACT: Introduction: Disturbances in the visual, vestibular, and oculomotor systems have been identified in Parkinson's disease (PD). Patients' perspectives regarding these symptoms remain unexplored and may provide insights on functional implications of these symptoms and guide future interventions. The goal of this study is to elicit perceptions of individuals with PD with respect to visual, vestibular, and oculomotor deficits. Methods : Twenty-nine individuals with PD participated in focus group discussions. Participants discussed visual, vestibular, and oculomotor deficits they experience and how these deficits affect function. Discussions were recorded, transcribed, and coded. Inductive qualitative data analysis techniques were used to interpret responses. Results : Four themes emerged: 1) participants perceived visual, vestibular, and oculomotor deficits and related these deficits to their PD diagnosis; 2) participants perceive that these deficits affect function; 3) participants suggested these deficits are not recognized by healthcare providers; and 4) participants indicated they receive limited treatment for these deficits. Conclusions : Visual, vestibular, and oculomotor deficits are under-reported and under-assessed symptoms, which have a significant impact on the lives of people with PD. Healthcare providers should be aware of such deficits. The findings suggest that the healthcare team can better identify these deficits and identify important future areas of research.